FETAL MUMMIFICATION IN GOAT: A CASE REPORT - Koli, A B; Ramteke, S S; Naktar, S B; Patil , A D (Animal Reproduction Update, 2023)
A three year old non-descript goat in fourth parity was presented to the Veterinary Clinical Complexes, COVAS, Udgir with the history of straining and vaginal discharge for last four to five hours. One live male fetus was delivered through obstetrical maneuvers which followed the delivery of mummified fetus. The goat was treated with fluid therapy, antibiotics, NSAID and antihistamines.